Emission of Selected Exhaust Gas Components and Fuel Consumption in Different Driving Cycles - Andrzej Kuranc; Jacek Caban; Branislav Šarkan; Agnieszka Dudziak; Monika Stoma (Communications - Scientific letters of the University of Zilina, 2021)
Road transport have significant impact on regional economic and social development, but one can also point out a number of its disadvantages, which include environmental pollution. The paper presents measurements of fumes exhaust emissions of a passenger car with a significant operational mileage. The tests were carried out in a laboratory on a chassis roller dynamometer using various driving cycles. To determine the exhaust emissions, data on the mass of air flowing through the intake manifold was used, among others. The work also describes an example of own driving cycle developed based on urban driving in Lublin, Poland.